A Review of Information and Communication Technologies Implementation in English Teaching and Learning in China - ZHANG, Hui (Journal of Research in Educational Sciences; Vol 12 No 1 (2021): JRES, Volume XII, Issue 1(14), 2021, 2021)
The usage of Information and Communication Technologies ( ICT) is a comprehensive reflection of teaching results. Generally teachers lack of motivation to use ICT in English teaching and some elder teachers are afraid of it. Therefore, research on ICT implementation in English teaching has attracted the attention of English educators. In this paper, we focus on teachers’ ICT Implementation which acts as an important role that directly influences students’ English performance. Also, 21 st century learning skill is introduced to help us more understand ICT. The paper will explore the language teachers’ ICT implementation in English class in China by investigating the reasons behind why they seldom use ICT. This study will also provide some solutions to help enhancing teachers’ motivations to use ICT in class.